KASUS-KASUS LEPTOSPIROSIS DI PERBATASAN KABUPATEN BANTUL, SLEMAN, DAN KULON PROGO: ANALISIS SPASIAL - , Maftuhah Nurbeti ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Leptospirosis is an important issue in Yogyakarta Province. Outbreak status had set in Sleman, Bantul, and Kulonprogo District. The border areas between these three districts play an important role and have the most cases. This study aims to analyze the spread of Leptospirosis incidence in the border region by finding out the distribution of the disease